Ramsay Hunt syndrome in atopic dermatitis patient treated with dupilumab - Čelakovská, Jarmila; Boudková, Petra; Wertzova, Veronika; Čáková, Lenka (International immunopharmacology, 2024)
The Ramsay-Hunt syndrome results from reactivation of the varicella-zoster virus at the geniculate ganglion level. The syndrome is characterized by a combination of symptoms such as ipsilateral facial paralysis, otalgia, and vesicles near the ear and auditory canal. The gold standard in the treatment of Ramsay-Hunt syndrome remains the combination of antiviral therapy with corticosteroids and adequate analgesic therapy. We present a case of a 45-year-old patient with severe form of atopic dermatitis, who developed this syndrome during treatment with dupilumab. The risks and benefits of dupilumab treatment in this patient were considered. Because both bronchial asthma and atopic dermatitis worsened when dupilumab was discontinued, it was indicated to continue this therapy with low-dose of acyclovir.
Keywords: Antiviral Agents; acyklovir; Dermatitis, Atopic; antivirové látky; Acyclovir; lidé; virus varicella zoster; Herpesvirus 3, Human; atopická dermatitida; Asthma; herpes zoster ušní; Herpes Zoster Oticus; Male; bronchiální astma; lidé středního věku; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; mužské pohlaví; Middle Aged; Humans